2018
DOI: 10.3390/ijms19030816
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin-Rich Extract from Red Chinese Cabbage Alleviates Vascular Inflammation in Endothelial Cells and Apo E−/− Mice

Abstract: Anthocyanins, the most prevalent flavonoids in red/purple fruits and vegetables, are known to improve immune responses and reduce chronic disease risks. In this study, the anti-inflammatory activities of an anthocyanin-rich extract from red Chinese cabbage (ArCC) were shown based on its inhibitory effects in cultured endothelial cells and hyperlipidemic apolipoprotein E-deficient mice. ArCC treatment suppressed monocyte adhesion to tumor necrosis factor-α-stimulated endothelial cells. This was validated by ArC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 38 publications
(41 reference statements)
1
26
0
2
Order By: Relevance
“…In previous studies, Joo et al evaluated the effects of anthocyanin‐rich extract from Red Chinese cabbage (RC) on vascular inflammation in endothelial cells and apolipoprotein E‐deficient mice. They reported that the major anthocyanin of the extract is cyanidin [186 mg/g (dry weight)] and found that the RC‐mediated suppression of transcription and expression of adhesion molecules correlated with lowering the risk of vascular inflammatory disease (Joo et al, ). Lee et al ( investigated and compared the contents of phenolic compounds in RC and typical green Chinese cabbage (GC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, Joo et al evaluated the effects of anthocyanin‐rich extract from Red Chinese cabbage (RC) on vascular inflammation in endothelial cells and apolipoprotein E‐deficient mice. They reported that the major anthocyanin of the extract is cyanidin [186 mg/g (dry weight)] and found that the RC‐mediated suppression of transcription and expression of adhesion molecules correlated with lowering the risk of vascular inflammatory disease (Joo et al, ). Lee et al ( investigated and compared the contents of phenolic compounds in RC and typical green Chinese cabbage (GC).…”
Section: Discussionmentioning
confidence: 99%
“…A review study reported that the synergistic effects of phytochemical extracts from fruits and vegetables have strong antioxidant and antiproliferative activities, and the major part of total antioxidant activity is from the combination of phytochemicals (Liu ). Studies for each single food such as Red Chinese cabbage, or Aronia related to anti‐inflammation and antioxidation are reported (Joo et al, ; Kokotkiewicz, Jaremicz, & Luczkiewicz, ), but the anti‐inflammatory effects with the mixture of Red Chinese cabbage and Aronia fruits have not been studied. Therefore, our objective was to investigate the anti‐inflammatory effect of mixtures of Red Chinese cabbage and Aronia (ARC) in LPS‐stimulated RAW 264.7 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Tel: +2348033762894. Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License the prevention of a number of human diseases such as breast cancer, prostate cancer, vascular inflammatory diseases and high blood pressure (National Cancer Institute, 2012;Higdon et al, 2017, Joo et al, 2018. Although cabbage has tremendous nutritional and medicinal benefits to the growth, development and health of humans, it has been reported to be susceptible to quite a number of diseases caused by pathogens such as fungi and bacteria (Weinberger and Lumpkin, 2005;Omokore et al, 2008Omokore et al, , 2009Mochiah et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Введение. В последние годы в развитых странах мира большое внимание уделяется организации здорового питания, обеспечивающего рост, нормальное развитие и жизнедеятельность человека и способствующего укреплению его здоровья и профилактики заболеваний [6,2,7,9,5].…”
unclassified
“…Сортимент краснокочанной капусты многочислен и весьма разнообразен по продолжительности вегетационного периода, морфологическим признакам, биологическим и хозяйственным свойствам. В различных почвенно-климатических зонах выращиваются определенные сорта и гибриды, адаптированные к местным условиям [6,7,4]. № 2 (54), 2019 5 F1 Super red F1 39,1 43,3 -32,2 36,1 ---Omero F1 33,0 42,9 38,1 38,0 103,5 28,3 37,3 33,5 33,0 104,1 Sx 0,…”
unclassified